2018
DOI: 10.3839/jabc.2018.007
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of Valeriana fauriei oils extracted by three different methods against Ricania shantungensis

Abstract: Ricania shantungensis is a pest causiong problems in many crops. We tested the possibility of controling Ricania shantungensis using essential oil of Valeriana fauriei which were extracted by three different methods (steam distillation, solvent and supercritical extraction). Steam distillation were showed the most high mortality to adult (1,040 µL/mL) and nymph (2,370 µL/mL) of R. shantungensis. The yield of steam distillation extraction was 0.67%, which was lower than other methods. However, it is determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, several studies have reported the insecticidal activity of different plant essential oils on both nymphs and adults of a Ricania sp. and O. japonica (Choi et al, 2012;Lee et al, 2016Lee et al, , 2018Jeon et al, 2016Jeon et al, , 2017Göktürk et al, 2017). Jeon et al (2016) tested the possible activity of essential oils from seven different plants on nymphs and adults of Ricania sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several studies have reported the insecticidal activity of different plant essential oils on both nymphs and adults of a Ricania sp. and O. japonica (Choi et al, 2012;Lee et al, 2016Lee et al, , 2018Jeon et al, 2016Jeon et al, , 2017Göktürk et al, 2017). Jeon et al (2016) tested the possible activity of essential oils from seven different plants on nymphs and adults of Ricania sp.…”
Section: Resultsmentioning
confidence: 99%
“…LC50 values for nymphs and adults were 31.3 and 62.4 mg/L, respectively, in another study by the same group. Lee et al (2018) tested the insecticidal effects of Valeriana officinalis L. (Dipsacales: Caprifoliaceae) essential oils extracted by steam distillation, solvent, and supercritical extraction on a Ricania sp. As a result, they observed that the extract obtained by steam distillation had the highest mortality for a Ricania sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the damage led to the designing of management (Baek et al, 2021) and sampling (Baek et al, 2020(Baek et al, , 2022 directives in the Republic of Korea (Baek et al, 2022). To mitigate damage, Jo et al (2016), Kim et al (2016), Lee et al (2018), Park et al (2017) and Ryu et al (2016) propose different chemical treatments, mostly with plant extracts, to repel or kill the pest.…”
Section: Impactsmentioning
confidence: 99%
“…The present updated taxonomic status is accessible online (Bourgoin, 2019 ). The species is also referred to as Ricania shantungensis Chou and Lu, 1977 in recent publications (Baek et al., 2019a , 2019b , 2020 , 2021 , 2022 ; Choi et al., 2011 ; Hizal et al., 2019 ; Kang et al., 2020 ; Kim et al., 2016 ; Kwon et al., 2017 ; Lee et al., 2018 ).…”
Section: Pest Categorisationmentioning
confidence: 99%